Effect of Dialysis on Erythropoietin and some Hematological Parameters in Patients with Chronic Renal Failure - Hayder, Zhian Sh.; Aziz, Jamal M.; Jaff, Mohamad Salih (Zanco Journal of Medical Sciences (ZJMS), 2009)
Background and objective: A prospective study was carried out for estimation the concentration of the erythropoietin hormone and its effects on some hematological parameters in chronic renal failure patients despite medical treatment. The object of the study was to evaluate the available evidences which support the relationship between anemia and adverse outcomes in chronic renal failure patients, to estimate the erythropoietin concentration of plasma in chronic renal failure patients and to examine the relationship between the anemia and erythropoietin concentration in patients with chronic kidney disease. Methods: One hundred and eleven (111) patients with CRF on dialysis in the Dialysis and Kidney Disease Center in Hawler Teaching Hospital and (40) control groups were studied. Haematological parameters: were performed by conventional manual methods. The quantitative measurement of erythropoietin concentration in serum was done by using the Erythropoietin ELISA kit (IBL Immuno Biological Laboratories Hamburg Erythropoietin Kit, German). Results: Hemoglobin, red blood cells, packed cell volume, and mean corpuscular hemoglobin were significantly decreased (P<0.001) in all age groups of Chronic renal failure patients, while, erythrocyte sedimentation rate and mean corpuscular volume (MCV) were increased significantly (P<0.001). Total white blood cells were decreased significantly (P<0.01) at the ages (40-60, >60) years groups, while not significantly decreased at the ages (<20, 20-40) years. Plasma erythropoietin was decreased significantly at the level (P<0.001) in chronic renal failure patients. Conclusion: Anemia is a common and often an early complication of chronic renal diseases and decreased renal production of erythropoietin is the major cause of anemia in these patients.